Anti-swing control for 2-D under-actuated cranes with load hoisting/lowering: A coupling-based approach. (December 2019) - li, Xue; Peng, Xiuhui; Geng, Zhiyong
Abstract: In this paper, we present a coupling-based anti-swing control for 2-dimensional (2-D) under-actuated cranes with load hoisting/lowering, which achieves precise trolley positioning, accurate load hoisting/lowering and efficient load swing suppression. Compared to the existing methods for cranes with load hoisting/lowering, this paper introduces a novel composite signal which enhances the coupling behavior between the actuated and under-actuated variables. Then, based on this signal and its derivatives, we constructed our controller without linearization or approximation operations to the original nonlinear crane model. In addition, some common assumptions related to the rope length and original model among existing works are further relaxed in this paper. Last, we provide numerical simulation results to validate the feasibility and effectiveness of the proposed controller. Highlights: The proposed controller gives an improved transient performance on swing suppression and elimination for control problem of overhead crane with load hoisting/lowering. Controller development and corresponding stability analysis are derived from original nonlinear system instead of a linearized one.